A molecular network-based pharmacological study on the protective effect of Panax notoginseng rhizomes against renal ischemia–reperfusion injury - Li, Dan-Dan; Li, Na; Cai, Chui; Wei, Chun-Mian; Liu, Guang-Hua; Wang, Ting-Hua; Xu, Fu-Rong (Frontiers in Pharmacology, 2023)
Objective: We aimed to explore the protective effect of Panax notoginseng rhizomes (PNR) on renal ischemia and reperfusion injury (RIRI) and the underlying molecular network mechanism based on network pharmacology and combined systemic experimental validation. Methods: A bilateral RIRI model was established, and Cr, SCr, and BUN levels were detected. Then, the PNR was pretreated 1 week before the RIRI model was prepared. To determine the effects of the PNR in RIRI, histopathological damage and the effect of PNRs to the kidney was assessed, using TTC, HE, and TUNEL staining. Furthermore, the underlying network pharmacology mechanism was detected by screening drug–disease intersection targets from PPI protein interactions and GO and KEGG analysis, and the hub genes were screened for molecular docking based on the Degree value. Finally, the expression of hub genes in kidney tissues was verified by qPCR, and the protein expression of related genes was further detected by Western blot (WB). Results: PNR pretreatment could effectively increase Cr level, decrease SCr and BUN levels, reduce renal infarct areas and renal tubular cell injury areas, and inhibit renal cell apoptosis. By using network pharmacology combined with bioinformatics, we screened co-targets both Panax notoginseng (Sanchi) and RIRI, acquired ten hub genes, and successfully performed molecular docking. Of these, pretreatment with the PNR reduced the mRNA levels of IL6 and MMP9 at postoperative day 1 and TP53 at postoperative day 7, and the protein expression of MMP9 at postoperative day 1 in IRI rats. These results showed that the PNR could decrease kidney pathological injury in IRI rats and inhibit apoptotic reaction and cell inflammation so as to improve renal injury effectively, and the core network mechanism is involved in the inhibition of MMP9, TP53, and IL-6. Conclusion: The PNR has a marked protective effect for RIRI, and the underlying mechanism is involved in inhibiting the expression of MMP9, TP53, and IL-6. This striking discovery not only provides fruitful evidence for the protective effect of the PNR in RIRI rats but also provides a novel mechanic explanation.